FORMATION OF PERSONALITY HARDINESS IN TODAY’S REALITIES (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2025)
Background.The article explores the complex processes of forming the hardiness of the individual in the conditions of the national struggle against the northern aggressor and the threat to Ukrainian society. The article’s purpose is to reflect and understand modernity through the prism of forming the hardiness of the individual. The multi-vector nature of the terms “geopolitics” and “society” is outlined. It is stipulated that our uniqueness is revealed thanks to the internal potential and opportunities in the social environment.Methods. Different approaches, such as systemic, activity-based, personality-oriented, and generally scientific methods, such as analysis of scientific literature, synthesis, generalization, and systematisation, were used to achieve the study's goals.Results. It is noted that the war causes disproportionate damage to each individual, the country’s development, personal well-being, and the environment. The reconstruction of the state of Ukraine should not be suspended, regardless of the state of war in the country, and the issues of the country’s restoration should be taken care of not only by the state, international and Ukrainian volunteer organisations but also by every citizen of Ukraine in particular. It is noted that the complex geopolitical situation of Ukraine is currently determined not by military, but by geopolitical trends that exist in the world today. The geopolitical situation of the state is complicated by the lack of a clear position of support for Ukraine by Western partners and the threat of curtailing constant international support for Ukraine’s military and critical infrastructure.
Keywords: society; formation; hardiness; war; state; life